Structure and potential anti-fatigue mechanism of polysaccharides from Bupleurum chinense DC. (15th April 2023) - Jiang, Peng; Ji, Xiang; Xia, Jing; Xu, Mengran; Hao, Fang; Tong, Haibin; Jiao, Lili
Abstract: Two polysaccharides, BCP-1 and BCP-2, were obtained from Bupleurum chinense DC. by water extraction and ultrafiltration. BCP-1 (1.04 × 10 5 Da) and BCP-2 (2.14 × 10 4 Da) were composed of Mannose, Rhamnose, Glucose, Galactose, Arabinose, and Galacturonic acid in different proportions. They both contained oligogalacturonides in their main chain. Besides, the backbone of BCP-1 was composed of 4-β-Gal p and 4, 6-β-Glc p, and branched at C4 of 4, 6-β-Glc p . While BCP-2 contained a backbone of 3, 5-α-Ara f residues with branches at C3. BCP-2 effectively extended the forced swimming time, improved the glycogen reserves and antioxidant system, decreased the levels of blood urea nitrogen, lactic acid, lactate dehydrogenase and creatinine kinase expression. It alleviated physical fatigue through regulating 5'-AMP-activated protein kinase (AMPK) and Nuclear Factor erythroid 2-Related Factor 2 (Nrf2) signalling pathway in skeletal muscles. This study demonstrated that BCP-2 exhibited more effective anti-fatigue activity than BCP-1 potentially associated with its primary and higher structures. Graphical abstract: Unlabelled Image Highlights: The crude polysaccharide BCP was obtained from Bupleurum chinense DC. Two fractions (BCP-1 and BCP-2) with different M w were obtained by ultrafiltration. BCP-2 was a heteropolysaccharide with triple helix structure. BCP-2 showed anti-fatigue activity via AMPK/PGC-1α and Nrf2/ARE signalling pathway.